Psychosocial Perspectives on Women's Involvement in Radicalism - Melaty Anggraini (Universitas Budi Luhur, 2024)
Abstrak: Peran perempuan alam radikalisme semakin dominan, seperti yang dibuktikan oleh banyak pelaku bom bunuh diri yang dilakukan oleh perempuan di seluruh dunia. Studi ini bertujuan untuk menganalisis faktor-faktor mendorong keterlibatan perempuan dalam radikalisme, dengan fokus pada perspektif psikologis perempuan yang terlibat. Penelitian ini menggunakan teori psikologi, yang berfokus pada aspek psikologis seperti aspek emosional, intelektual, biologis, dan perilaku, yang dipengaruhi oleh aspek sosial dari fungsi manusia. Kombinasi faktor pribadi dan sosial, juga dikenal sebagai faktor psikososial, dilihat sebagai aspek yang tak terpisahkan dari pemahaman proses radikalisasi, termasuk perilaku teror atau kecenderungan radikalisasi. Faktor psikologis yang dipengaruhi oleh faktor sosial sering menyebabkan gejala psikososial seperti trauma, yang menyebabkan krisis identitas pribadi dan disfungsi perilaku. Inilah sebabnya mengapa rekrutmen kelompok teroris menggunakan krisis identitas sebagai pedoman dalam merekrut dan menemukan kandidat. Memahami faktor-faktor psikologis ini diperlukan untuk mencegah perempuan terlibat dalam tindakan radikalisme dengan menyentuh emosi mereka dan memulihkan kembali rasa kemanusian dan empati pelaku. Pemahaman ini akan membantu mencegah perempuan terlibat dalam aliran kelompok terorisme dan terhindar dari kelompok ekstremis. Abstract: The shift in the role of women in the involvement of radicalism has not been seen much on the surface, but it has been found that women's involvement is increasingly dominating as evidenced by the many actions of suicide bombers carried out by several women globally. For this reason, this study will focus on analyzing the driving factors of their involvement in radicalism, but more on the context of the psychological perspectives of the women involved to find the most appropriate approach in helping the prevention and control process for women exposed to radicalism. This research uses the theory of psychoanalysis proposed by Sigmund Freud, which focuses on psychological aspects such as emotional, intellectual, biological, and behavioral, which are influenced by social aspects of human functioning to form patterns of human personality and understanding the development of their character. The combination of personal (psychological) factors and social factors, also called psychosocial, is seen as one of the inseparable aspects in understanding the process of radicalization including terror behavior or radicalized tendencies. The analysis of the theory found that the relevance of psychological factors is very influential on personality and human actions to carry out acts of radicalism. Psychological factors influenced by social factors often cause psychosocial symptoms such as trauma which causes a personal identity crisis that sometimes makes a person experience loss of identity and consciousness and act dysfunctional. Individuals experiencing identity crises will be easily influenced and indoctrinated, which is why some recruiters of terrorist groups are well aware of this, and use it as a cornerstone in recruiting and finding recruits. Therefore, understanding in the context of a psychological perspective is needed to prevent women from engaging in acts of radicalism by touching their emotions by reinstalling the human spirit and empathy of perpetrators who are lost due to traumatic feelings or psychosocial conditions they experience. Understanding their social identity crisis and the traumatic sense that drives involvement in radicalism will help prevent women from becoming involved in the maelstrom of terrorism and avoid identifying with extremist groups.